2014
DOI: 10.1177/1352458514530489
|View full text |Cite
|
Sign up to set email alerts
|

Responder definition of the Multiple Sclerosis Impact Scale physical impact subscale for patients with physical worsening

Abstract: Background:The 29-item Multiple Sclerosis Impact Scale (MSIS-29) was developed to examine the impact of multiple sclerosis (MS) on physical and psychological functioning from a patient’s perspective.Objective:To determine the responder definition (RD) of the MSIS-29 physical impact subscale (PHYS) in a group of patients with relapsing–remitting MS (RRMS) participating in a clinical trial.Methods:Data from the SELECT trial comparing daclizumab high-yield process with placebo in patients with RRMS were used. Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 29 publications
3
45
1
Order By: Relevance
“…The differences between the groups were statistically significant (physical impact score, p   <  0.001) or tended towards significance (psychological impact score, p   =  0.068). Further analysis of the trial data suggested that an increase of ≥7.5 on the MSIS-29 physical scale could be considered indicative of clinically relevant increase (deterioration) [60]. Using this MCID, the proportion of patients with MSIS-29 physical deterioration at 52 weeks was lower in the daclizumab group than in the placebo group (20 vs. 28%; p   <  0.01).…”
Section: Impact Of Dmds On Health-related Quality Of Lifementioning
confidence: 99%
“…The differences between the groups were statistically significant (physical impact score, p   <  0.001) or tended towards significance (psychological impact score, p   =  0.068). Further analysis of the trial data suggested that an increase of ≥7.5 on the MSIS-29 physical scale could be considered indicative of clinically relevant increase (deterioration) [60]. Using this MCID, the proportion of patients with MSIS-29 physical deterioration at 52 weeks was lower in the daclizumab group than in the placebo group (20 vs. 28%; p   <  0.01).…”
Section: Impact Of Dmds On Health-related Quality Of Lifementioning
confidence: 99%
“…Only 14 out of 82 PROs evaluated had an overall mean score above the threshold of 50 (Table S1). Here results are presented for the eight MS-specific PROs that were most commonly used instruments in MS clinical trials, namely Multiple Sclerosis Impact Scale-29 (MSIS-29) [12][13][14][15][16][17][18][19][20][21], Leeds Multiple Sclerosis Quality of Life (LMSQoL) [22][23][24], Multiple Sclerosis Walking Scale-12 (MSWS-12) [25][26][27][28][29][30], Functional Assessment of Multiple Sclerosis [15,18,[31][32][33], Hamburg Quality of Life Questionnaire in Multiple Sclerosis (HAQUAMS) [34][35][36], Multiple Sclerosis International Quality of Life (MUSIQoL) questionnaire [37,38], Patient-Reported Indices for MS Activity Limitations Scale (PRIMUS) [39][40][41] and Multiple Sclerosis Quality of Life-54 (MSQoL-54) [18,[42][43][44][45][46]. The characteristics of these eight PROs are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The FDA-published guidance for industry includes information on how it evaluates existing, modified or new PROs used to support labeling claims. Although the The rationale for and description of the concept and the populations that a measure is intended to assess and the relationship between them Reliability (items [8][9][10][11][12][13][14][15] The degree to which an instrument is free from random error Validity (items [16][17][18][19][20][21] The degree to which the instrument measures what it purports to measure Responsiveness (items 22-24)…”
Section: Study Limitationsmentioning
confidence: 99%
“…Thresholds for clinically meaningful worsening in the MSIS-29 PHYS subscale score have been established in both the clinical trial and the community setting [17,18]. Clinically meaningful worsening in the MSIS-29 PHYS subscale score was reported as ≥7.5 points in a clinical trial population [17] and ≥ 7.0 points in a community setting [18], for subjects with MS and an EDSS score of 0 to 5 [17]. For subjects based in a community setting with an EDSS score of 5.5 to 8, the clinically meaningful threshold for MSIS-29 PHYS subscale worsening was reported as ≥ 8 points [18].…”
Section: Discussionmentioning
confidence: 99%
“…Thresholds for a clinically meaningful change in the MSIS-29 PHYS have been proposed to be between 7 and 8 points [17,18]. Therefore, analyses were also conducted to evaluate the percentages of subjects who achieved a ≥7-point improvement in the MSIS-29 PHYS subscale score, by MSIS-12 improver status.…”
Section: Improvements In the Msis-29 Phys Subscale According To Msws-mentioning
confidence: 99%